(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Teachers are the pillars of our nation. Teacher plays an important part in developing the knowledge and skills of youth. Role of teacher in society and in education can change but, the importance of their position remains same. Job satisfaction is only possible if the job fulfills the basic needs of teachers in term of salary and better status. This study was to evaluate the job satisfaction of elementary school teachers in Ajmer. In this research, the sample was made up of 90 teachers of government non- government schools. Results indicate that teachers job satisfaction is medium level. In addition, in order to provide additional information about satisfaction with the current job, pleasure with life in the workplace, desire for job change, and desire for early retirement. The study provides results based on teachers married and unmarried, rural and urban, gender and, teaching.